"Like I'm a nobody:" firearm-injured peoples' perspectives on news media reporting about firearm violence - Jessica H. Beard; Jennifer Midberry; Iman N. Afif; Elizabeth Dauer; Jim MacMillan; Sara F. Jacoby (Elsevier, 2023)
Media reports on interpersonal firearm violence largely present it as a crime issue focused on individual shooting events. This episodic framing can undermine support for public health solutions to firearm violence. Potential harms of this narrative on firearm-injured people are unknown. We aimed to understand how recently firearm-injured people perceive the meaning and impact of news media reporting on their own injuries and on firearm violence in their communities. This study was conducted in the trauma clinic of the busiest trauma center for firearm injuries in Philadelphia, PA, USA. We consecutively recruited adult firearm-injured patients for semi-structured qualitative interviews within two months of their injury. Interview content was thematically analyzed. Twenty-six patients consented and participated. Results indicate that participants largely felt negative or conflicted about "making the news" and perceived several harms associated with media reports on their injuries, including dehumanization they connected with episodic-style reports, reliving trauma when viewing news, distress related to inaccuracies, threats to personal safety when specific details were included, harm to reputation, and negative impacts on public perceptions of safety and community. Participants who did not make the news often reported relief and generally did not expect their story to be reported. These findings suggest that firearm-injured people perceive multiple harms associated with episodic narratives that neglect their own viewpoints. Journalists and public health practitioners should work together with communities to identify strategies to reframe firearm violence as a public health problem through reporting that is trauma-informed and incorporates the perspectives of firearm-injured people.